Representasi Akulturasi Budaya pada Relief Rumah Adat Lontiok di Kabupaten Kampar - Maijar, Lidia; Sudarman, Sudarman; Aisyah, Siti; Andri, Adetia (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study describes the background, existence, and function of Lontiok Traditional Houses, the traditional dwellings of the Malay ethnic group in Kampar Regency, Riau Province, Indonesia. Employing a historical method, the research focuses on archaeological reliefs as the primary source and interviews as the secondary source. Source criticism ensures data authenticity and reliability, while data interpretation involves field analysis and literature review. Findings reveal that Lontiok Traditional Houses are not merely physical structures but also embody traditional art and Minangkabau cultural continuity. The intricate carvings preserve cultural traditions and educate Kampar's younger generation. These houses, reflecting high values of customs, art, and culture, serve as cultural tourist attractions and venues for traditional events such as leadership installations, deliberations, and weddings. The inauguration on May 22, 1988, on Belimbing Island highlights their significance in preserving Minangkabau cultural heritage.